English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-11-28 12:09:00 · 6 answers · asked by Kamikaze Pilot 2 in Science & Mathematics Mathematics

6 answers

Substitute y(0)=1 into y= -1/(-cos x + c)

1 = -1/(-cos0 + c)
1 = -1/(-1 + c)
-1 + c = -1
c = -1 + 1
c = 0

2006-11-28 12:32:12 · answer #1 · answered by Kemmy 6 · 0 0

cos (0) = 1 so c = 0.

2006-11-28 12:14:41 · answer #2 · answered by Anonymous · 0 0

If you mean y(x) = -1/(-cos(x) + c), then

y(0) = -1/(-cos(0) +c).

But cos(0) = 1.

So, y(0) = -1/(-1 + c).

So, y(0) = 1 if and only if c = 0.

2006-11-28 12:13:57 · answer #3 · answered by oddy411 1 · 0 0

put in values for y(0)=1
1=-1/(-1+c)
(-1+c)= -1
c=0

therefore,y= -1/(-cos x + c), y(0)=1
iff c=0

i hope that this helps

2006-11-28 21:23:33 · answer #4 · answered by Anonymous · 0 0

i want to use my calcualtor but i lost my fingers yesterday!
wha! whaa!
: (
'
'

2006-11-28 12:50:29 · answer #5 · answered by Anonymous · 0 0

penguin

2006-11-28 12:12:21 · answer #6 · answered by Anonymous · 0 0

fedest.com, questions and answers